ANALISIS KETERLIBATAN PENULIS BERDASARKAN JENIS KELAMIN DALAM PUBLIKASI JURNAL BAREKENG - Maloky, Jessica Kezia; Rumaropen, Teodora Jessical; Bakarbessy, Lusye; Patty, Dyana; Lesnussa, Yopi Andry (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Professional scientific journal management requires transparent, inclusive, and data-driven governance practices, including in terms of author involvement based on gender. This article aims to analyze the involvement of male and female authors in Berekeng journal publications as part of the reflection and contribution of the scientific journal management profession. The method used is quantitative descriptive analysis that analyzes the dynamics of gender participation in scientific publications during the 2007–2025 period. The results of the study show that the 2007–2018 period was significantly dominated by male authors (peaking at 84.44% in 2018). However, there was a rapid transition towards balance in 2019–2021, where female participation began to prevail (54.63% in 2021). This pattern continued in the 2023–2025 period, showing a new significant dominance by female authors (peaking at 56.45% in 2024). Overall, the total number of female authors (50.81%) slightly exceeded that of male authors (49.19%). This dramatic shift implies a fundamental change in the academic community. Specifically in the context of Mathematics, this trend is predicted to encourage diversification of research topics into Applied Mathematics and Data Science, strengthen interdisciplinary collaboration, and create a more inclusive research environment. This study concludes that gender equality efforts have fundamentally changing the landscape of publishing. These activities are expected to strengthen the capacity of journal managers in implementing data-driven management while promoting fair and sustainable scientific publishing practices as a tangible manifestation of professional dedication in the field of scientific journal management.